Plastic limit load of ellipsoidal pressure vessel head with nozzle under internal pressure loading - Skopinsky, Vadim N.; Smetankin, Andrey Borisovich; Berkov, N.A. (Zielona Góra: Uniwersytet Zielonogórski)
A new method and numerical procedure for determining the plastic limit load in an ellipsoid-cylinder intersection using the elastic-plastic finite element analysis are presented. The proposed method is based on the maximum criterion of the rate of change of the relative plastic work. For the elastic-plastic analysis of the nozzle connections the 2D finite element method and plasticity theory with strain hardening are used. The results of the comparison of the plastic limit pressure obtained on the basis of different known criteria and the proposed criterion are presented. A parametric study of ellipsoidal heads with a nozzle under internal pressure loading was performed. The effects of nondimensional geometric parameters of shell intersection on the plastic limit pressure are discussed.
Keywords: shell intersection; elastic-plastic finite element analysis; plastic limit load; ellipsoidal head; nozzle connection